IMPLEMENTASI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN: (KHUSUS) UNTUK PENGENDARA SEPEDA MOTOR DI KOTA SEMARANG - Chintya Elva Yuliana; Hartuti Purnaweni; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Motorcycle is one of risky transportation in traffic accident. This accident is caused by motorcycles aren’t equipped with special safety. Often the motorcyclist are also less attention of safety riding, with traffic violations that could harm other riders. The traffic policeman as a law enforcer seem slow in taking action againts the traffic violations. The aim of this research is to know how the implementation of law No. 22 of 2009 About Traffic and Road Transportation: (Special) for Motorcyclist in Semarang, by using phenomenons of implementation effectivity they are appropriateness of the police, implementor, target, and enviroment. Also to know about support and resistor factor by using implementation model George Edward III wich is mention four factors that influence the implementation they are communivation, resources, dispotition, and bureaucracy structure. This research is use descriptive qualitative research method. The result of this research shown the implementation of law No. 22 of 2009 About Traffic and Road Transportation: (Special) for Motorcyclist in Semarang has been going well and effective. This can be seen from the phenomenoms of implementation effectivity that can be reached. Although has been going effective its still have resistor factors. So needs adding some traffic policeman, budgeting, fasilities, information system, to over come the problem of traffic, enforcement of stict sanctions for traffic policeman that misuse authority.